Familial neuronal intranuclear inclusion disease complicated by subcortical hemorrhage. Issue 3 (13th January 2019) - Mitsutake, Akihiko; Tamai, Tomohisa; Kamisawa, Aya; Sugiyama, Yusuke; Sato, Tatsuya; Katsumata, Junko; Seki, Tomonari; Maekawa, Risa; Hideyama, Takuto; Saito, Yuko; Shiio, Yasushi
Abstract: An 80‐year‐old woman presented with loss of appetite. At age 78, she was diagnosed as familial neuronal intranuclear inclusion disease (NIID) based on (i) leukoencephalopathy with hyperintensities along the corticomedullary junction on diffusion‐weighted imaging (DWI) revealed by brain magnetic resonance imaging (MRI), (ii) skin biopsy samples showing ubiquitin‐positive intranuclear inclusions in adipocytes, and (iii) family history. Her cognitive function was preserved while apathy was apparent. However, on this admission, her cognitive function got worse. Afterward, the patient developed subcortical hemorrhage, and the risk for the hemorrhage was not identified. NIID might be associated with intracranial hemorrhage. In addition, brain MRI after the bleeding showed the rapid expansion of hyperintense lesions on DWI even in the frontal lobe where bleeding was irrelevant. Intracranial hemorrhage might have affected the enlarged hyperintense lesions.